Negative pole piece, preparation method of negative pole piece, battery and power utilization device
By adopting a multi-layer composite structure in the negative electrode sheet, including transition layers of nano-scale carbon powder and porous ceramics and a negative electrode active material layer designed with gradient particle size, it is solved that traditional negative electrode sheets are difficult to meet high energy density and long cycle life. Problem, significantly improving the electrochemical and safety performance of the battery.
Patent Information
- Application Number
- CN202411183528.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-27
- Publication Date
- 2024-12-20
AI Technical Summary
Traditional negative electrode sheets have limitations in structural design and material selection, and it is difficult to meet the needs of high energy density and long cycle life.
Using a multi-layer composite structure including a current collector, a transition layer and a negative electrode active material layer, the transition layer is arranged on the current collector surface, the negative electrode active material layer is arranged on the transition layer surface, the transition layer includes nano-scale carbon powder and/or porous ceramics, and the negative electrode The active material layer is prepared by continuous coating technology and heat treatment using gradient particle size design and combination of conductive agents and binders.
It significantly improves the electrochemical performance, energy density and cycle life of the battery, optimizes the transmission path of lithium ions in the electrode sheet, enhances the binding force between the current collector and the negative electrode active material layer, avoids the loosening and powder loss of the negative electrode active material, and improves the The safety performance of the battery.
Smart Images

Figure CN119170746A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of batteries, and in particular to a negative electrode plate and a preparation method thereof, as well as a battery and an electrical device. Background Art
[0002] With the development of new energy vehicles, portable electronic devices and other fields, the requirements for the energy density, cycle stability and other performance of lithium-ion batteries are increasing. As a key component of lithium batteries, the performance of the negative electrode directly affects the overall performance of the battery. Traditional negative electrode sheets have limitations in structural design and material selection, and it is difficult to meet the requirements of high energy density and long cycle life. Therefore, the development of new negative electrode sheet technology has become a hot topic in current research. Summary of the invention
[0003] In view of this, the purpose of the present application is to provide a negative electrode sheet and a preparation method thereof, so that the negative electrode sheet can significantly improve the electrochemical performance, energy density and cycle life of the battery;
[0004] Another object of the present application is to provide a battery and an electrical device based on the above-mentioned negative electrode plate.
[0005] In order to solve the above-mentioned technical problems / achieve the above-mentioned purposes or at least partially solve the above-mentioned technical problems / achieve the above-mentioned purposes, as a first aspect of the present application, a negative electrode plate is provided, comprising a current collector, a transition layer and a negative electrode active material layer; the transition layer is arranged on at least one surface of the current collector, the negative electrode active material layer is arranged on at least one surface of the transition layer, and the transition layer comprises nano-scale carbon powder and / or porous ceramics.
[0006] Optionally, the negative electrode active material layer includes a first negative electrode active material layer, a second negative electrode active material layer and a third negative electrode active material layer which are stacked in sequence, or includes a first negative electrode active material layer and a third negative electrode active material layer which are stacked in sequence; the third negative electrode active material layer is disposed on at least one surface of the transition layer; the negative electrode active material D of the first negative electrode active material layer 50 >Negative electrode active material D of the second negative electrode active material layer 50 >Negative electrode active material D of the third negative electrode active material layer 50 .
[0007] Further optionally, the negative electrode active material D of the first negative electrode active material layer 50 The negative electrode active material D of the second negative electrode active material layer is 15-25 μm. 50 The negative electrode active material D of the third negative electrode active material layer is 5-15 μm. 50 1-5μm.
[0008] Optionally, the negative electrode active material layer includes a negative electrode active material, and the negative electrode active material is graphite. Further optionally, the negative electrode active material layer also includes a conductive agent and a binder.
[0009] Optionally, the pore size of the porous ceramic is 10-100 nm.
[0010] As a second aspect of the present application, a method for preparing the negative electrode sheet is provided, comprising:
[0011] Obtaining transition layer slurry and negative electrode active material layer slurry;
[0012] The various layers are sequentially coated on the current collector using a continuous coating technique, and then heat treated to obtain the negative electrode sheet.
[0013] As a third aspect of the present application, a battery is provided, comprising the negative electrode plate described in the present application.
[0014] Optionally, it is a lithium-ion battery, comprising a positive electrode plate, a separator, an electrolyte, and the negative electrode plate described in the present application, and the positive electrode active material of the positive electrode plate comprises lithium iron phosphate.
[0015] As a fourth aspect of the present application, an electrical device is provided, comprising the battery described in the present application.
[0016] The present application optimizes the structure of the negative electrode plate, adds a transition layer between the current collector and the negative electrode active material layer, and adopts a multi-layer composite structure to construct the negative electrode plate, so as to optimize the transmission path of lithium ions in the plate, while improving the binding force between the current collector and the negative electrode active material layer, avoiding loosening and powdering of the negative electrode active material, thereby improving the safety performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application.
[0018] Figure 1 Shown is a schematic diagram of the structure of the negative electrode sheet described in this application;
[0019] Figure 2 Shown is a schematic diagram of the structure of the negative electrode sheet described in this application;
[0020] Figure 3 Shown are the room temperature 1C / 1C cycle curves of Examples 1-3 of the present application. DETAILED DESCRIPTION
[0021] The present application discloses a negative electrode plate and a method for preparing the same, as well as a battery and an electrical device. Those skilled in the art can refer to the contents of this article and appropriately improve the process parameters to achieve the same. It should be particularly noted that all similar substitutions and modifications are obvious to those skilled in the art, and they are all deemed to be included in this application. The products, processes and applications described in this application have been described through preferred embodiments. Relevant personnel can obviously modify or appropriately change and combine the products, processes and applications described in this article without departing from the content, spirit and scope of this application to realize and apply the technology of this application. Obviously, the described embodiments are part of the embodiments of this application, not all of them. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0022] It should be noted that, in this article, if relational terms such as "first" and "second", "step 1" and "step 2", and "(1)" and "(2)" appear, they are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "comprise", "include" or any other variants thereof are intended to cover non-exclusive inclusion, so that the process, method, article or equipment including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or equipment. In the absence of further restrictions, the elements defined by the sentence "comprise one..." do not exclude the presence of other identical elements in the process, method, article or equipment including the elements. At the same time, the embodiments in this application and the features in the embodiments may be combined with each other without conflict.
[0023] In the first aspect of the present application, a negative electrode sheet is provided, comprising a current collector, a transition layer and a negative electrode active material layer; the transition layer is disposed on at least one surface of the current collector, the negative electrode active material layer is disposed on at least one surface of the transition layer, and the transition layer comprises nano-scale carbon powder and / or porous ceramics. The negative electrode active material layer is at least two layers, the transition layer is at least one layer, and the current collector is a metal foil, such as a copper foil or an aluminum foil with good conductivity.
[0024] In certain embodiments of the present application, the negative electrode active material layer includes a first negative electrode active material layer, a second negative electrode active material layer and a third negative electrode active material layer and they are stacked in sequence, or includes a first negative electrode active material layer and a third negative electrode active material layer and they are stacked in sequence; the third negative electrode active material layer is disposed on at least one surface of the transition layer; it can be understood that the negative electrode active material particles in the negative electrode active material layer adopt a gradient particle size distribution design, that is, the particle size of the particles close to the current collector is smaller, and the particle size of the particles away from the current collector is larger. This design helps to reduce the diffusion distance of lithium ions in the negative electrode active material layer and improve the charge and discharge efficiency. In addition, since the small-particle-size negative electrode active material particles are closer to the current collector in the battery, they are closer to the pole ear, which helps to avoid lithium deposition at the head of the lithium battery and reduce the consumption of the electrolyte; while the large-particle-size negative electrode active material particles are relatively far away from the pole ear, which helps to improve the wettability of the electrolyte. Therefore, this design can simultaneously improve the lithium deposition and electrolyte consumption problems of the lithium battery during use and improve the battery performance.
[0025] In certain embodiments of the present application, the negative electrode active material D of the first negative electrode active material layer 50 >Negative electrode active material D of the second negative electrode active material layer 50 >Negative electrode active material D of the third negative electrode active material layer 50 In some other embodiments of the present application, the negative electrode active material D of the first negative electrode active material layer 50 The negative electrode active material D of the second negative electrode active material layer is 15-25 μm. 50 The negative electrode active material D of the third negative electrode active material layer is 5-15 μm. 50 For example, the negative electrode active material D of the first negative electrode active material layer 50 The negative electrode active material D of the second negative electrode active material layer is 20 μm. 50 The negative electrode active material D of the third negative electrode active material layer is 10 μm. 50 5μm.
[0026] In some embodiments of the present application, the negative electrode active material layer includes a negative electrode active material, and the negative electrode active material is graphite. In other embodiments of the present application, the negative electrode active material layer also includes a conductive agent and a binder. In other embodiments of the present application, at least one layer of the negative electrode active material layer includes a conductive agent and a binder at the same time, and the remaining layers can only add a binder, and the mass percentage of the negative electrode active material: conductive agent: binder in each layer is 96-98.9%: 0.1-1%: 1-3%; wherein the conductive agent includes one or more of carbon black conductive agents, carbon nanotube conductive agents, conductive graphite conductive agents, graphene conductive agents and carbon fiber conductive agents. Among them, carbon black conductive agents include conductive carbon black SP, Ketjen black and acetylene black. Carbon nanotubes and graphene are used in the implementation of this application to improve the conductivity of the pole piece and the lithium ion migration rate. The binder includes water-based PVDF, PAA, SBR, CMC, etc. In the implementation process of this application, water-based PVDF and PAA are used to improve the adhesion between the negative electrode active material and each layer while maintaining a high ionic conductivity.
[0027] In certain embodiments of the present application, the transition layer includes nano-scale carbon powder and / or porous ceramics, and a binder, wherein the binder has a mass percentage of 1-3%, and the remainder is nano-scale carbon powder and / or porous ceramics.
[0028] In some embodiments of the present application, the pore size of the porous ceramic is 10-100 nm. A pore size that is too small affects lithium ion migration and has a high cost; a pore size that is too large affects processing performance. In other embodiments of the present application, the porous ceramic is a porous alumina ceramic.
[0029] In a second aspect of the present application, a method for preparing the negative electrode sheet is provided, comprising:
[0030] Obtaining transition layer slurry and negative electrode active material layer slurry;
[0031] The various layers are sequentially coated on the current collector using a continuous coating technique, and then heat treated to obtain the negative electrode sheet.
[0032] The transition layer slurry is prepared by using water as solvent, adding a water-based binder, and nano-scale carbon powder and / or porous ceramics.
[0033] The negative electrode active material layer slurry is prepared by dissolving the negative electrode active material, the conductive agent and the binder in water or an organic solvent, and adjusting the slurry to meet the required viscosity.
[0034] The obtained slurry is coated with a high-precision continuous coating device to achieve precise coating of the multilayer structure, ensuring uniformity and consistency between the layers, and the thickness of each layer is 1-5 μm. The coated negative electrode sheet is heat treated to remove the solvent, improve the crystallinity and stability of the material, and promote the uniform distribution of the conductive agent in the active material layer. In certain embodiments of the present application, the heat treatment includes treatment at 200°C ± 50°C for 1-5 hours.
[0035] In a third aspect of the present application, a battery is provided, comprising the negative electrode plate described in the present application.
[0036] In certain embodiments of the present application, it is a lithium-ion battery, including a positive electrode sheet, a separator, an electrolyte, and a negative electrode sheet as described in the present application, and the positive active material of the positive electrode sheet includes lithium iron phosphate. The lithium-ion battery includes, but is not limited to, a soft-pack battery, a button battery, a half-cell or a full battery. In certain embodiments of the present application, a soft-pack lithium-ion battery is provided, wherein the positive electrode sheet active material is composed of lithium iron phosphate, PVDF, and conductive carbon black SP, and the negative electrode sheet active material is respectively composed of the above graphite, conductive carbon black SP, sodium carboxymethyl cellulose CMC, and styrene-butadiene rubber SBR, and the separator adopts a 16μmPP base film. The electrolyte contains 1mol / L LiPF6, EC:EMC:DEC (mass ratio 25:40:30) and VC2%. The negative electrode sheet, separator and positive electrode sheet are stacked in a Z shape to form a soft-pack battery, with a designed N / P of 1.15 and a designed capacity of 3Ah.
[0037] In a fourth aspect of the present application, an electric device is provided, comprising the lithium-ion battery described in the present application, wherein the lithium-ion battery provides electric energy for the electric device. The electric device may be various devices or equipment driven by the lithium-ion battery, including but not limited to electric vehicles, electric vehicles, self-balancing vehicles, flatbed vehicles, aircraft, lighting equipment, household appliances, etc.
[0038] In each group of comparative experiments provided in this application, unless otherwise specified, other experimental conditions, materials, etc. are kept consistent except for the differences indicated in each group, so as to provide comparability. The experimental materials and reagents used in the examples can be obtained from commercial channels unless otherwise specified.
[0039] The following is a further description of a negative electrode plate and a preparation method thereof, as well as a battery and an electrical device provided in the present application.
[0040] Embodiment 1:
[0041] The negative electrode sheet consists of a current collector layer, a transition layer and two negative electrode active material layers (the first and third negative electrode active material layers). See the structural diagram for Figure 1The transition layer is a nano-scale carbon powder layer with a thickness of about 1 μm; the third negative electrode active material layer is a small-particle graphite layer (D50=5 μm), and the first negative electrode active material layer is a large-particle graphite layer (D50=15 μm), both of which are 20 μm thick.
[0042] Material selection: 1wt% carbon nanotubes are added to the small-diameter graphite layer; 0.5wt% graphene is added to the large-diameter graphite layer. The binder is 2wt% water-based PVDF.
[0043] Preparation process: Each layer is coated on the current collector in sequence using continuous coating technology, and then heat treated at a temperature of 200°C for 2 hours.
[0044] Embodiment 2:
[0045] On the basis of Example 1, a medium-sized graphite layer (D50=10 μm) is added, namely the second negative electrode active material layer, which is located between the first and third negative electrode active material layers. The structural schematic diagram is shown in Figure 2 , in order to further optimize the lithium ion transmission path. Others refer to Example 1.
[0046] Graphite in different particle size layers has different conductivity and expansion during the charge and discharge process. Graphite with small particles has fast ion migration, but large contact impedance and expansion. On the contrary, large-particle graphite prevents the gap between negative electrode active material particles from becoming larger during the charge and discharge process by constructing a conductive network with a reasonable gradient, thereby ensuring the conductivity of the negative electrode sheet and facilitating the cycle performance.
[0047] Embodiment 3:
[0048] A porous ceramic layer is used as a transition layer between the negative electrode active material layer and the current collector layer (replacing the nanoscale carbon powder layer). This layer has excellent ionic conductivity and mechanical strength, and can significantly improve the cycle stability of the electrode.
[0049] Material selection: The porous ceramic layer is made of alumina ceramic material with a pore size of 10-100 nm. The other layer structures are the same as those in Example 2.
[0050] Preparation process: Before coating the active material layer, firstly apply ceramic slurry and sinter to form a porous ceramic layer. Other steps refer to Example 2.
[0051] Porous ceramics will increase the safety and structural stability of the battery. The negative electrode will be buffered in the pores of the ceramic layer during its expansion process, which can effectively alleviate the problem of loosening and powdering of the negative electrode active material during long-term use.
[0052] Comparative Example 1:
[0053] Based on Example 1, no transition layer is added, and other aspects remain the same;
[0054] Comparative Example 2:
[0055] Based on Example 1, graphite with D50=10 μm was uniformly used to form the negative electrode active material layer, and other aspects remained the same
[0056] Comparative Example 3:
[0057] Based on Example 1, the transition layer material is replaced with normal ceramic alumina, which is not sintered to form a porous structure, and the other parts remain the same;
[0058] Experimental example:
[0059] Detection Methods
[0060] (1) At room temperature, charge at a constant current of 1C to 3.65V, and then charge at a constant voltage (3.65V) to a cut-off current of 0.05C;
[0061] (2) Leave for 10 minutes;
[0062] (3) 1C constant current discharge to 2.0V;
[0063] (4) Leave for 10 minutes;
[0064] (5) Jump to step (1), cut-off condition: cycle to the target number of cycles or capacity retention rate ≤ 80%.
[0065] The cycle performance curves of Examples 1-3 are shown in Figure 1 The capacity retention rate data of each embodiment and comparative example are shown in Table 1;
[0066] Table 1
[0067] Capacity retention rate after 500 cycles at 1C at room temperature Capacity retention rate after 800 cycles at room temperature and 1C Example 1 98.63% 96.85% Example 2 98.12% 97.54% Example 3 96.47% 95.01% Comparative Example 1 97.55% 93.11% Comparative Example 2 97.16% 92.67% Comparative Example 3 91.23% 86.42%
[0068] Combination Figure 1 As shown in Table 1, among the embodiments, the cycle performance of Embodiment 1 and Embodiment 2 is better. Embodiment 3 uses an insulating porous ceramic layer as a transition layer, so its internal resistance is relatively high and its capacity is not as good as that of Embodiment 1 and Embodiment 2. However, the addition of the porous ceramic layer will improve the safety and structural stability of the battery. The capacity retention rate of Embodiment 2 at 500 cycles is slightly lower than that of Embodiment 1, but its advantages begin to emerge when it cycles to 800 cycles.
[0069] Compared with Example 1 and Example 2 and the comparative examples, the capacity retention rate of Example 1 and Example 2 shows significant performance advantages at both 500 and 800 cycles; the retention rate of the porous ceramic transition layer of Example 3 at 500 cycles is lower than that of Comparative Examples 2 and 3, but as the number of cycles increases, its structural stability and ion transmission path advantages gradually emerge.
[0070] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.
Claims
1. A negative electrode plate, characterized in that: It includes a current collector, a transition layer and a negative electrode active material layer; the transition layer is arranged on at least one surface of the current collector, the negative electrode active material layer is arranged on at least one surface of the transition layer, and the transition layer includes nano-scale carbon powder and / or porous ceramics.
2. The negative electrode sheet according to claim 1, characterized in that: The negative electrode active material layer comprises a first negative electrode active material layer, a second negative electrode active material layer and a third negative electrode active material layer which are sequentially stacked, or comprises a first negative electrode active material layer and a third negative electrode active material layer which are sequentially stacked; the third negative electrode active material layer is arranged on at least one surface of the transition layer; the negative electrode active material D of the first negative electrode active material layer 50 >Negative electrode active material D of the second negative electrode active material layer 50 >Negative electrode active material D of the third negative electrode active material layer 50 .
3. The negative electrode sheet according to claim 2, characterized in that: The negative electrode active material D of the first negative electrode active material layer 50 The negative electrode active material D of the second negative electrode active material layer is 15-25 μm. 50 The negative electrode active material D of the third negative electrode active material layer is 5-15 μm. 50 1-5μm.
4. The negative electrode sheet according to any one of claims 1 to 3, characterized in that: The negative electrode active material layer includes a negative electrode active material, and the negative electrode active material is graphite.
5. The negative electrode sheet according to claim 4, characterized in that: The negative electrode active material layer further includes a conductive agent and a binder.
6. The negative electrode sheet according to claim 1, characterized in that: The pore size of the porous ceramic is 10-100 nm.
7. The method for preparing the negative electrode sheet according to claim 1, characterized in that: include: Obtaining transition layer slurry and negative electrode active material layer slurry; The various layers are sequentially coated on the current collector using a continuous coating technique, and then heat treated to obtain the negative electrode sheet.
8. A battery, characterized in that: A negative electrode sheet comprising the negative electrode sheet according to any one of claims 1 to 6.
9. The battery according to claim 8, characterized in that It is a lithium-ion battery, comprising a positive electrode plate, a separator, an electrolyte, and a negative electrode plate as described in any one of claims 1 to 6, wherein the positive electrode active material of the positive electrode plate comprises lithium iron phosphate.
10. An electrical device, characterized in that: A battery comprising the battery of claim 8 or 9.
